Fabrication of SiO2/PEGDA Inverse Opal Photonic Crystal with Fluorescence Enhancement Effects - Van-Phuc Dinh; Duy-Khoi Nguyen; Quang-Hung Nguyen; Thi-Thuy Luu; Thi Hai Yen Pham; Thi Thu Ha Vu; Han-Sheng Chuang; Hong-Phong Pham (Journal of Analytical Methods in Chemistry)
The present paper reports the fabrication of inverse opal photonic crystals (IOPCs) by using SiO2 spherical particles with a diameter of 300 nm as an opal photonic crystal template and poly(ethylene glycol) diacrylate (PEGDA) as an inverse opal material. Characteristics and fluorescence properties of the fabricated IOPCs were investigated by using the Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), reflection spectroscopy, and fluorescence microscopy. The results clearly showed that the IOPCs were formed comprising of air spheres with a diameter of ∼270 nm. The decrease in size led to a decrease in the average refractive indexes from 1.40 to 1.12, and a remarkable stopband blue shift for the IOPCs was thus achieved. In addition, the obtained results also showed a fluorescence enhancement over 7.7-fold for the Fluor® 488 dye infiltrated onto the IOPCs sample in comparison with onto the control sample.